Practice and Experience in the Standardization of Third - Party Service Management for Government Informatization - Dong, Yaoyi; Lin, Minrui; Zhen, Jiong (Innovative Applications of AI, 2025)
The introduction of third - party services has become a key way to enhance professional support and project management in government informatization projects. However, practical problems such as vague service content, lack of unified standards, weak evaluation mechanisms, serious talent loss, and lack of industry cooperation platforms have limited project quality and the effectiveness of digital government construction. Guangdong Province has explored third - party service standardization by building a service standard system, strengthening talent training, and improving evaluation mechanisms, offering replicable practical experience for the whole country.